Visualization and Manipulation of Neural Activity in the Developing Vertebrate Nervous System - Zhang, Jiayi; Ackman, James; Dhande, Onkar S.; Crair, Michael C. (Frontiers in Molecular Neuroscience, 2011)
Neural activity during vertebrate development has been unambiguously shown to play a critical role in sculpting circuit formation and function. Patterned neural activity in various parts of the developing nervous system is thought to modulate neurite outgrowth, axon targeting and synapse refinement. The nature and role of patterned neural activity during development has been classically studied with in vitro preparations using pharmacological manipulations. In this review we discuss newly available and developing molecular genetic tools for the visualization and manipulation of neural activity patterns specifically during development.